Pendampingan Pengelolaan Kelestarian dan Kesehatan Lingkungan Hidup bagi Generasi Z Kelurahan Klasuur Distrik Sorong Papua Barat Daya - Pattiwael, Maya; Metanfanuan, Tia; Turot, Amatus (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This community service activity aims to increase the knowledge and awareness of Gen Z with the hope that they can pass on the knowledge they have gained to other people around them as well as become an example in implementing an attitude of caring for the environment. PKM is carried out in the form of socialization using lecture and question and answer methods to explore activity partiicipants knowledge abaout environmental sustainability and health.. Service activities take place in several stages, namely preliminary study, preparation, implementation and evaluation. The delivery of material is more directed at participants knowlegde about the environment, environmental problems, concern for the environment, benefits obtained and several activities that Gen Z can carry out in maintaning environmental sustainability and health. The excitement of the participants could be seen from the many questions asked of the presenters. Likewise, at the evaluation stage, several questions to test participants memory and understanding of the material can be answered well. Mentoring for Generation Z needs to continue to be carried out to motivate them to be more active in protecting their environment.